Image of Afterlife in Medieval Plastic Art of Abkhazia - Endoltseva, Ekaterina (IKON, 2011)
Abstract The article deals with the problem of identification and dating of a stone relief which is conserved in the Abkhazian State museum in Sukhum. Due to iconographical parallels with some Palestinian floor mosaics of the 6th-7th centuries, the image of a bull and a lion near the cross carved on the above-mentioned slab can be regarded as an illustration of the Isaiah’s prophecy (11.7). The analysis of the evolution of this iconographical motif as well as archaeological, historical and epigraphic context permits to date it by the 11th century. In medieval period it was used in decoration of the sepulchral monuments being associated with death and Resurrection.